IEEE International Conference on Advanced Learning Technologies, 2004. Proceedings.
DOI: 10.1109/icalt.2004.1357442
|View full text |Cite
|
Sign up to set email alerts
|

Learning style and factors contributing to success in an introductory computer science course

Abstract: An introductory course in computer science (CS1) is required of virtually all engineering majors at the University of Minnesota Duluth. From 2001-present an extensive battery of visualization software was developed for this course. Students consistently ranked the visualization software as more important to their learning than any other element of the course. However, these rankings were not highly correlated with actual outcomes. This study of learning style determined that reflective and verbal learners outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1
6

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 11 publications
4
26
1
6
Order By: Relevance
“…For example, Chamillard and Karolick report that the reflective and verbal learners performed better than others [16]. Similar findings are reported by [17] and [18].…”
Section: Analysis On Academic Performancesupporting
confidence: 83%
“…For example, Chamillard and Karolick report that the reflective and verbal learners performed better than others [16]. Similar findings are reported by [17] and [18].…”
Section: Analysis On Academic Performancesupporting
confidence: 83%
“…They concluded that whilst learning style was not significant, it was noticeable that there was a preponderance of Convergers who had selected the programming course, an area which warrants further study. Similarly, Gomes and Mendes [12] found little or no correlation between the achievement and learning style of first year programming students, however Allert [13] reported a difference. Goold and Rimmer [14] maintain that students with a high relative abstraction score tend to do well in computing, a position that is supported by the results of this study.…”
Section: The Converging Style (Think and Do) Ac/aementioning
confidence: 96%
“…Another model is the Myers and Briggs Type Indicator (MBTI) (Myers, 1962) that was based on personality types. However, Allert (2004) stated that there were two dominant learning style assessment tools used in science and engineering education. For Kolb's KLSI and Felder-Silverman's (LSI), both these models measured four different dimensions of an individual's learning style.…”
Section: Review Of Literaturementioning
confidence: 99%